COMPUTATIONAL ANALYSIS AND FUNCTIONAL ANNOTATION OF AP2/ERF TRANSCRIPTION FACTOR BINDING SITES IN ARABIDOPSIS THALIANA L. GENOME - O. A. Chernykh; V. G. Levitsky; N. A. Omelyanchuk; V. V. Mironova (Вавиловский журнал генетики и селекции)
The plant hormone ethylene regulates both developmental processes and various stress responses in plants. Ethylene perception in plants is followed by activation of some transcription factors from the large family of APETALA2/ETHYLENE response factors (ERFs). ERF TF binding sites contain a specific GCCGCC motif, called GCC-box. In this study, we applied TF binding site recognition tools oPWM and SiteGA for sequence analysis of experimentally proven GCC-boxes. We carried out GCC box recognition and tested its distribution in the Arabidopsis thaliana L. genome. Functional annotation and microarray data analysis of the genes possessing predicted GCC-boxes elucidated their role in ethylene response.